The inflammatory response between miniaturised and conventional cardiopulmonary bypass after cardiac surgery in an Asian population. (September 2015) - Ng, RRG; Chew, STH; Liu, W; Ong, P; Caleb, MG; Ti, LK
Introduction: We compared the systemic inflammatory response of the MCPB system to the CCPB system with cell salvage and phosphorylcholine-coated tubing amongst Asian patients undergoing coronary artery bypass grafting. Methods: Seventy-eight patients were randomly assigned to the MCPB or the CCPB groups equally and followed up in a prospective, single-blinded, randomised, controlled trial. Levels of TNF-α, IL-6, CRP and LDH were measured peri-operatively. Results: The systemic inflammatory response was similar in both groups (TNF-α: p=0.222; IL-6: p=0.991; CRP: p=0.258). Only haemolysis was significantly higher in the CCPB group (LDH: p=0.011). The MCPB system was twice more expensive, but had a near 4-fold cost saving in tranfusions. Overall, the MCPB system cost 20% more than the modified CCPB system. Conclusion: These results corroborate with studies that demonstrated the avoidance of cardiotomy suction rather than the MCPB system, itself, leads to an attenuated inflammatory response. The absence of obvious clinical benefit and the higher costs involved with the MCPB system would preclude its routine use.